Emotional intelligence in front-line/back-office employee relationships - Kearney, Treasa; Walsh, Gianfranco; Barnett, Willy; Gong, Taeshik; Schwabe, Maria; Ifie, Kemefasu (The Journal of services marketing, 2017)
Purpose This paper aims to undertake a simultaneous assessment of interdependence in the behaviours of front-line and back-office employees and their joint effect on customer-related organisational performance. It also tests for a moderating influence of the emotional intelligence of front-line salespeople and back-office employees. Design/methodology/approach The sample comprises 105 front-line sales employees and 77 back-office employees. The customer-related organisational performance data come from a UK business-to-business (B2B) electronics company. With these triadic data, this study uses partial least squares to estimate the measurement and structural models. Findings Salespeople’s customer orientation directly affects customer-related organisational performance; the relationship is moderated by salespeople’s emotional intelligence. The emotional intelligence of salespeople also directly affects the customer-directed citizenship behaviour of back-office employees. Furthermore, the emotional intelligence of back-office staff moderates the link between the emotional intelligence of salespeople and back-office staff citizenship behaviour. Back-office staff citizenship behaviour, in turn, affects customer-related organisational performance. Originality/value The emotions deployed by employees in interactions with customers clearly shape customers’ perceptions of service quality, as well as employee-level performance outcomes. However, prior literature lacks insights into the simultaneous effects of front-line and back-office employee behaviour, especially in B2B settings. This paper addresses these research gaps by investigating triadic relationships – among back-office employees, front-line employees and customer outcomes – in a B2B setting, where they are of particular managerial interest.